(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The role of social sciences in shaping the spiritual education of youth is crucial in fostering a well-rounded and holistic development in today’s fast-paced, complex society. This article examines how the integration of social science disciplines—such as sociology, psychology, anthropology, and history—into educational curricula can contribute to the moral and spiritual growth of young individuals. By focusing on ethical reasoning, social responsibility, and critical thinking, social sciences provide youth with the tools to navigate their personal values, beliefs, and societal norms. The article discusses the intersection between social sciences and spiritual education, exploring how understanding human society, culture, and history can enhance youths’ spiritual awareness, empathy, and moral compass. It also highlights the challenges and opportunities faced by educators in delivering this kind of education in modern classrooms. Ultimately, this article emphasizes the importance of an interdisciplinary approach to education in fostering the moral, ethical, and spiritual well-being of the next generation.